Pronoun Interpretation in the Second Language: Effects of Computational Complexity - Slabakova, Roumyana; White, Lydia; Brambatti Guzzo, Natália (Frontiers in Psychology, 2017)
Children acquiring their native language (L1) have been reported to have greater difficulty in interpreting pronouns than reflexives. In addition, they are less accurate when pronouns refer to referential antecedents than to quantified antecedents, and when they hear full pronouns as opposed to reduced pronouns. We hypothesize that similar difficulties of interpretation will occur for (non-advanced) second language (L2) learners, due to an elevated computational burden, as argued for L1 acquisition by Reinhart (2006, 2011). We report on an experiment with adult learners of English (L1s French and Spanish), using a truth-value judgment task. Participants interpreted reduced and full pronouns bound by referential and quantified antecedents in aurally presented test sentences. The learners’ performance is affected by type of pronoun and antecedent. When a referential antecedent is combined with a full pronoun, learners’ accuracy is significantly lower. These results are in line with Reinhart’s analysis of reference set computation in processing pronouns.